PENERAPAN UNDANG-UNDANG NO. 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG DALAM PERKARA TINDAK PIDANA KORUPSI OLEH KEJAKSAAN TINGGI SUMUT - Taufik Taufik; Madiasa Ablisar; Sunarmi Sunarmi; Mahmud Mulyadi (USU LAW JOURNAL, 2019)
ABSTRACT For a Public Prosecutor (JPU) it is not easy to verify the indictment in the corruption case in the court, especially in the case of corruption, the evidence and the witnesses are numerous, it requires a team to do so. It takes courage, intelligence, professionalism in performing the proofing process, such as summoning witnesses, summoning experts, showing presenting evidence of letter and other evidence in front of the trial. The whole process of the trial required a skill. In addition to proving the indictment, in the case of handling corruption cases, the public prosecutor should also make every effort to recover the state's financial losses. In the case of Corruption, the public prosecutor has the right to give an indictment, but when viewed in the current corruption cases the public prosecutor often neglects and weakly performs duties and authority in the case of indictment. In the case of criminal acts of corruption, sometimes the public prosecutor is less assertive in giving indictments and processing cases of corruption. The emphasis of indecision here can be seen from the prosecutor's charges that are handling corruption cases, never using money laundering offenses in the indictment. Actually, Law no. 8 Year 2010 on Prevention and Eradication of Money Laundering Crime (hereinafter referred to as "TPPU Law") has been enacted since October 22, 2010 which aims to make the state financial loss so great that it can be returned to the state. Therefore, there is no weakness in the legislation in Indonesia to ensnare the perpetrators of corruption. The device already exists only live snared alone. The perpetrator of a corrupt crime must return all the proceeds of his crime to the state. Keywords : money laundering; corruption; high attorney office of north sumatra.